\[\boxed{\text{216\ (216).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ ( - a)^{2} \cdot a^{3} = a^{2} \cdot a^{3} = a^{5}\]
\[2) - a^{2} \cdot a^{3} = - a^{5}\]
\[3)\ a^{2} \cdot ( - a)^{3} = - a^{5}\]
\[4) - a^{2} \cdot ( - a)^{3} = a^{5}\]
\[\boxed{\text{216.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[= - 17m - 6\]
\[Получим\ из\ левой\ части\ \]
\[равенства\ правую:\]
\[= - 17m - 6\]
\[- 17m - 6 = - 17m - 6\]
\[\Longrightarrow тождество\ доказано.\]
\[2)\ a + b - 10ab =\]
\[Получим\ из\ правой\ части\ \]
\[равенства\ левую:\]
\[\ a + b - 10ab =\]
\[\ a + b - 10ab = a + b - 10ab\]
\[\Longrightarrow тождество\ доказано.\]
\[= 5a - \left( 3a - (2a - 4) \right)\]
\[Преобразуем\ каждую\ часть\ \]
\[равенства:\]
\[= 5a - (3a - 2a + 4)\]
\[4a - 4 = 5a - a - 4\]
\[4a - 4 = 4a + 4\]
\[\Longrightarrow тождество\ доказано.\]